1981
DOI: 10.1007/bf00006123
|View full text |Cite
|
Sign up to set email alerts
|

The physico-chemical hydrology of a tropical seasonal river-upper Ogun river

Abstract: Materials and methodsThe physico-chemical properties of the Ogun River were recorded between January 1974 and December I975. A wet season with mean monthly rainfall of 9.72 cm. (s.d. = 5.07 cm) occurred from April through October, while a dry season with mean monthly rainfall of 0.56 cm. (s.d. = o.99 cm) occurred between November and March. The seasonal changes in the rainfall of the drainage area resulted in an alternation of the hydrological regimes of the river. The high water level of the river that arose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
68
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 8 publications
14
68
2
Order By: Relevance
“…The Composition of phytoplankton community of the ponds agreed with reports that blue-green algae and green algae dominate most tropical water bodies (Adebisi, 1981;Ayodele & Ajani, 1999). Increased temperature, sunlight and tropholytic activities as a result of low water level coupled with frequent movement of water from the deep, nutrient-rich sediments into the tropholytic zone, increased the abundance of phytoplankton during dry season.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The Composition of phytoplankton community of the ponds agreed with reports that blue-green algae and green algae dominate most tropical water bodies (Adebisi, 1981;Ayodele & Ajani, 1999). Increased temperature, sunlight and tropholytic activities as a result of low water level coupled with frequent movement of water from the deep, nutrient-rich sediments into the tropholytic zone, increased the abundance of phytoplankton during dry season.…”
Section: Discussionsupporting
confidence: 86%
“…Changes in the intensity of rainfall affects physico-chemical parameters of water which also affects biomass of aquatic organisms (Adebisi, 1981). The higher turbidity, salinity, TDS and most of the physico-chemical properties in the wet season had been explained to be as a result of flooding during heavy rainfall and run-off from nutrient rich agricultural lands increased (Ayodele & Ajani 1999;Offem, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The phytoplankton composition in this study agreed with reports of Adebisi (1981) and Ayodele and Ajani (1999) that blue-green algae and green algae dominate most tropical African waters. The dominance of Chlorophyceae in respect of species number and population density in this study had also been observed elsewhere (Tressler et al, 1940;Willen, 1959;Vyverman, 1996, Silva, 2005 and the overwhelming presence in the dry season, attributed to the presence of bright sunshine and extensive catchment area, draining calcium rich agriculture land (Pennack, 1949;Kurasawa and Shiraishi, 1954;Lewis, 1996).…”
Section: > Phytoplanktonsupporting
confidence: 92%
“…In other places, the intensity of waterfalls andpressure generated from it due to gravity has given the im-pression of a lifeless zone [1]. Knowledge of waterfalls systems in Africa are therefore limited to hydrology and geological features [2,3], as natural monuments for revenue generation, because of their ecotourism potentials [4] and as source for drinking, irrigation and other domestic purposes. Studies on the fisheries and aquaculture tuarine and open water body systems.…”
Section: Introductionmentioning
confidence: 99%